Factors Related to the Completeness of Electronic Surgical Safety Checklist Documentation in Banyumas Public Hospital - Halimatus Sya’diyah; Kris Linggardini (Proceedings Series on Health & Medical Sciences, 2024)
Background: Patient safety in surgery is a program established by the WHO and is a standard for accreditation by KARS, implementing the electronic surgical safety checklist. This has been proven to reduce patient safety incidents in the surgical room. Method: This quantitative research used a descriptive correlation design with a cross-sectional approach. A total sampling technique was employed, involving 34 surgical nurses in the Central Surgical Installation of RSUD Banyumas, who met the inclusion and exclusion criteria. The research instrument utilized an observation sheet based on the surgical safety checklist Standard Operating Procedure (SPO) at RSUD Banyumas. Data analysis was conducted using the chi-square test. Results: The results of the study revealed that the majority of nurses were male (70.6%), aged between 31-40 years (41.2%), and above 40 years (41.2%), with a DIII level of education (70.6%), and work experience of 1-5 years (44.1%), and they completed the electronic surgical safety checklist documentation (67.6%). Age, education level, and work experience correlate with the completeness of electronic surgical safety checklist documentation at RSUD Banyumas (p-value ? ?). Conclusion: Age, education level, and work experience related to the completeness of electronic surgical safety checklist documentation at RSUD Banyumas.